OGM and WES identifies translocation breakpoints in PKD1 gene in an polycystic kidney patient and healthy baby delivered using PGT - Peiwen Xu; Lijuan Wang; Jing Li; Sexin Huang; Ming Gao; Ranran Kang; Jie Li; Hongqiang Xie; Xiaowei Liu; Junhao Yan; Xuan Gao; Yuan Gao (BMC, 2023)
Abstract Background Autosomal dominant polycystic kidney disease (ADPKD) is one of the most common autosomal dominant genetic diseases. Whole exome sequencing (WES) is a routine tool for diagnostic confirmation of genetic diseases, and it is usually performed to confirm the clinical diagnosis in ADPKD. Reciprocal translocation is the most common chromosomal structural abnormalities and most of its carriers have normal phenotypes until they are encountered infertility problems in adulthood. However, for the polycystic kidney disease caused by abnormal chromosome structure, WES is difficult to achieve the purpose of gene diagnosis. Methods ADPKD-related genes were detected by WES; Chromosomal karyotyping and Optical Genome Mapping (OGM) were used to detect structural variant; The genomic break-point locations and the abnormal splicing were detected by reverse transcription-PCR and Sanger sequencing; The karyomapping gene chip and Next-Generation Sequencing (NGS) were performed to screen aneuploidy and to distinguish the non-carrier embryos from the carrier embryos. Results No pathogenic variant was found after the first round of WES analysis. Karyotyping data showed 46, XX, t (16; 17) (p13.3; q21.3). With the help of OGM, the translocation breakpoint on chromosome 16 was located within the PKD1 gene. With re-analysis of WES raw data, the breakpoint of translocation was verified to be located at the c.10618 + 3 of PKD1 gene. Based on this molecular diagnosis, a non-carrier embryo was selected out from three blastocysts. With preimplantation genetic testing (PGT) after in vitro fertilization (IVF), it was then transferred into uterus. With confirmation by prenatal and postnatal testing, the pedigree delivered a healthy baby. Conclusion We identified a case of ADPKD caused by balanced translocation and assisted the patient to have a healthy child. When the phenotype was closely related with a monogenic disease and the WES analysis was negative, chromosomal structural analysis would be recommended for further genetic diagnosis. Based on the precision diagnosis, preventing the recurrence of hereditary diseases in offspring would be reachable.